A study of incidence and risk factors of Surgical site infection following orthopedic surgical procedure in a tertiary care hospital in south India - Ali Mohammed P; Deep Sharma; D K Patro; Jagdish Menon; Murali Poduval (International Journal of Medical Research and Review, 2015)
Introduction: Surgical site infection following orthopaedic surgeries is a particularly catastrophic complication. So identification and stratification of risk factors of surgical site infection is utmost important in implementation of measures to prevent surgical site infection.Materials and Methods: This study was done in JIPMER Puducherry between January 2013 and August 2014. We aimed at identifying the incidence of surgical site infection and also tried to find out the factors associated with a higher risk for SSI. We studied a total of 249 patients, and collected their demographic data as per our proforma and at the end of the study data was compared among two groups of patients (patients with SSI vs Patients without SSI).Results: We found in our study that the incidence of patients developing surgical site infection as 11.6% (29 patients). BMI (>25), use of C arm, duration of surgery (>3 hours), duration of closed suction drain (>2 days) and amount of collection of drain (>170 ml) are risk factors of post-operative wound discharge and infection.Conclusion: The present study shows that incidence of surgical site infection in our patient population is11.6%, and out of various parameters studied we found that, BMI, use of C-arm, blood transfusion, duration of closed suction drain and amount of collection in suction drain to be important risk factors for the development of surgical site infection